The impact of dental operating microscopes on the success rates of endodontic treatments - Alshargawi, Waleed K.; Almazrua, Abdulaziz I.; Tobaigy, Roaa A.; Alsagoor, Wafqah H.; Almossaen, Mohammad B.; Moafa, Waleed M.; Alharbi, Rahaf M.; Kehaili, Ohud A.; Alqahtani, Mohammed S.; Alfaraj, Hawra Z.; Zamim, Khawlah A. (International Journal Of Community Medicine And Public Health, 2023)
Recent advancements in dental technology, such as magnification devices like loupes and surgical microscopes, have greatly improved the accuracy and quality of root canal treatments. Dental operating microscopes (DOMs) have become widely accepted in endodontics, providing enhanced visualization and facilitating precise identification of anatomical landmarks, root canal orifices, and pulp remnants. The increased magnification and illumination offered by DOMs have improved treatment outcomes by enabling more efficient removal of bacteria, debris, and obturation materials from the root canal system. Studies have shown that the use of DOMs can significantly increase the success rates of endodontic treatments, allowing for the identification and treatment of even the smallest canals and anatomical variations. Additionally, DOMs enhance ergonomics, patient communication, and documentation in dental practice. However, challenges such as cost and limited office space hinder their widespread use. Increased education and awareness of the benefits of operating microscope utilization are essential for its broader adoption in endodontic procedures.